2006
DOI: 10.1002/ijc.21705
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and mammographic density in a multiethnic population

Abstract: This report examined the association between alcohol intake and breast cancer risk as assessed by mammographic densities in a multiethnic population. Information for this analysis was available from 2 previous investigations: a nutritional intervention study (The Breast, Estrogens, and Nutrition Study; BEAN) with 217 premenopausal women and a nested case-control study within The Multiethnic Cohort (MEC) with 1,250 primarily postmenopausal women. On the basis of self-reported alcohol intake from a validated foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 33 publications
6
22
0
Order By: Relevance
“…There is no consistent agreement in the literature on the association between alcohol consumption and mammographic density [21][22][23][24][25][26][27][28][29][30][31][32][33]. Our results of no association are consistent with results from several other studies [30][31][32][33].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…There is no consistent agreement in the literature on the association between alcohol consumption and mammographic density [21][22][23][24][25][26][27][28][29][30][31][32][33]. Our results of no association are consistent with results from several other studies [30][31][32][33].…”
Section: Discussionsupporting
confidence: 89%
“…Some studies support a weak but significant positive association between alcohol intake and mammographic density in both pre-and postmenopausal women [21][22][23][24][25]. Other studies report a nonsignificant positive trend of increasing mammographic density with increasing intake [26][27][28][29] or a null association [30][31][32][33]. There is limited data on the association between alcohol intake, alcohol type and mammographic density.…”
Section: Introductionmentioning
confidence: 96%
“…Cigarette smoking status was not associated with breast density in a univariate model but showed some evidence of an association in the multivariate analysis. Alcohol consumption was not significantly associated with breast density but rose with increasing alcohol use in line with previous publications (18). Time since stopping HRT and family history of breast cancer were not significantly associated with density in either model, but there were few women who had ever taken HRT or with a family history of breast cancer.…”
Section: Methodssupporting
confidence: 88%
“…Our results agree with other studies that have found weak or no association between alcohol intake and breast density [17,29,16,30], which like ours reported a low average alcohol intake (average intake range of <0.1–5.35 g/day (<0.5 servings/day)) [17] or a low percentage of women consuming ≥7 drinks/week (<5%) [29]. In our study, 64% of women were current drinkers; however, only 13% consumed >7 servings/week.…”
Section: Discussionsupporting
confidence: 93%